Artikel review: Perawatan tradisional Indonesia bagi ibu pada masa nifas - Lola Aprilia; Neneng Rachmalia Izzatul Mukhlishah (Universitas Mataram, 2023)
Indonesia is a country that has a variety of cultures. The ethnic groups that are widespread in Indonesia have diverse cultures with their own characteristics. Culture is believed to be useful in aspects of life, one of which is related to medicine. Traditional medicine in Indonesia is a unique culture passed down from time to time, from one generation to another. This treatment is more sought after by the community because it is easy to obtain and affordable. This article purpose is to provide an overview of traditional treatments in Indonesia from several regions in Indonesia from Sabang to Merauke. This review contains care for mothers in the postpartum period from the characteristics of each region by utilizing typical Indonesian plants that grow in the surrounding environment. The cultural heritage related to this treatment is still maintained and is carried out by some people.